The Relationship Between the Motif of Memory/Remembrance and One of Its Aspects Concerning the Command to Exterminate the Canaanites in Deuteronomy 7 = Zvʼjazok miž motyvom pamʼjati / pam’jatuvannja ta odnym iz joho aspektiv, ščo stosujetʹsja nakazu vynyščyty chanaanejan u Vtorozakonni 7 - Lukin, Volodymyr (Bogoslovs'ki rozdymi, 2025)
This article explores the specific features of the theological connection between the motif of memory/remembrance and one of its aspects, namely, the command to exterminate the seven nations of Canaan. It is argued that viewing the world through the lens of covenant doctrine, which defines the foundation and essence of the connection itself in the book of Deuteronomy, is imperative in nature. As a result, the study does not dispute the legitimacy of violence. Instead, it reasserts necessity for this practice in the context of God's evolving relationship with His people at specific border periods of the event-time continuum. That means that the violence mentioned in the book of Deuteronomy 7 is theologically vindicated. Also, for the first time in a discussion of this kind, the necessary negative and positive elements (destruction and freedom) that shaped the content and form of corporate memory generated by two fundamental events in the history of the people of Israel (Egypt and the conquest of Canaan) were identified. The text highlights both the theoretical and practical nuances of "remembrance," and the specifics of its worldview theological adversary — the motif of forgetting.